On the influence of structural and chemical properties on the elastic modulus of woven bone under healing - Blázquez-Carmona, Pablo; Mora-Macías, Juan; Pajares, Antonia; Mármol, Álvaro; Reina-Romo, Esther (Frontiers in Bioengineering and Biotechnology, 2024)
Woven bone, a heterogeneous and temporary tissue in bone regeneration, is remodeled by osteoblastic and osteoclastic activity and shaped by mechanical stress to restore healthy tissue properties. Characterizing this tissue at different length scales is crucial for developing micromechanical models to optimize mechanical parameters which control regeneration and prevent non-unions. This study examines the temporal evolution of the mechanical properties of bone distraction callus using nanoindentation, ash analysis, micro-CT for trabecular microarchitecture, and Raman spectroscopy for mineral quality. It also defines single-and two-parameter power laws based on experimental data to predict tissue and bulk mechanical properties. At the macro-scale, the tissue exhibited a considerable increase in the bone fraction controlled by the widening of trabeculae, which play a more significant role than their chemical composition in the apparent elastic modulus of the tissue. Raman mineral-to-matrix ratio rose to cortical bone levels during regeneration, but the local elastic modulus remained lower, likely due to trabecular microporosities. Raman parameters were demonstrated to provide more significant power laws correlations with the micro-scale elastic modulus than mineral content from ash analysis.